Enhancing the diagnostic yield of monogenic diabetes in unresolved cases with early-onset hyperglycemia - Pedro Campos Franco (Communications Medicine, 2025)
Abstract Background To improve the precision of molecular diagnosis by means of a comprehensive bidirectional phenotypic and genotypic reanalysis in cases of unresolved monogenic diabetes previously investigated using a targeted next-generation sequencing (tNGS) panel. Methods Molecular and clinical data from 128 unresolved cases referred between 2011 and 2019 were analyzed. These included 92 cases of suspected maturity-onset diabetes of the young (MODY), 12 of neonatal diabetes, 16 of familial partial lipodystrophy (FPLD), 7 of mitochondrial diabetes, and 1 of Wolfram syndrome. All cases were initially investigated using a tNGS panel consisting of 51 nuclear genes and the complete mitochondrial genome. Results This extensive reanalysis process increases molecular diagnosis from 9 to 22%. Phenotypic reevaluation, entailing in-depth phenotyping, is instrumental in excluding 62 atypical cases (48.4%). Genotypic reanalysis identifies 5 previously overlooked molecular defects: two mutations in regulatory regions (one in the HNF1A promoter and another in the PTF1A enhancer); one in the MTTK mitochondrial gene; one in the MFN2 gene; and one in the GCK gene. Conclusions Our findings indicate that a combined approach of genotypic and, mainly, phenotypic reanalysis is an effective strategy for improving the accuracy of molecular diagnosis in individuals with suspected monogenic diabetes.